Success is the only option the art of coaching extreme talent - Calipari, John 1958-; Sokolove, Michael Y. (Harper, an imprint of HarperCollinsPublishers, 2016)
The basketball coach for the University of Kentucky, known for recruiting some of the nation's best players, explains how his team-building methods can help business owners, teachers, and other leaders inspire talented people and unleash their true potential.